Sensorial and physicochemical characteristics of herbal noodle enriched with centella asiatica - Fadzil, N.F.; Abu Bakar, M.F.; Yusop, M.H.M.; Abu Bakar, F.I. (Rynnye Lyan Resources, 2020)
Centella asiatica is one of the traditional herbs found commonly in Malaysia. It has been used as an important ingredient in many traditional medicine practices due to its antioxidant and pharmacological properties. This study was done by adding three different percentages of C. asiatica extracts (20%, 40% and 60%) in noodles. Sensory evaluation involving appearance, colour, taste and aroma (affective test), physicochemical properties (texture, pH and colour), antioxidant activity (DPPH, FRAP, TPC and TFC assays) and nutritional composition on control noodle and herbal noodles enriched with C. asiatica were conducted. For sensory test, control noodle is the most favorable followed by 60% herbal noodle. There was a reduction in the firmness of cooked 20% and 60% herbal noodles. The pH value of herbal noodles also decreased as the concentration of herbal noodles increased due to the addition of C. asiatica. Colour analysis showed that the L* values of all the samples were increased, a* values decreased which indicated strong green colour among the herbal noodles while b* values showed the highest value for control noodle. Antioxidant tests such as DPPH showed that 60% herbal noodle exhibited higher free radical scavenging with a value of 49.200% as compared to control noodle (16.027%). The same finding was observed for FRAP assay where 60% herbal noodle displayed higher value (111.335 μg/mL) than control noodle (71.233 μg/mL). TFC of 60% herbal noodle also showed the highest value as compared to other noodles. However, TPC of 40% herbal noodles had greater value as compared to 60% herbal noodle. A decrease in the nutritional value of herbal noodle compared to control noodle was also observed. In conclusion, herbal noodles enriched with C. asiatica showed promising antioxidant potential which can be used in functional food applications.